Off-Label 9-Valent Human Papillomavirus Vaccination for Actinic Keratosis: A Case Series - Emily Wenande; Niels Bech-Thomsen; Katrine Togsverd-Bo; Merete Haedersdal (Karger Publishers, 2021)
Background: The suspected link between human papillomavirus (HPV) and the development of premalignant and malignant skin lesions remains inadequately examined in clinical settings. This case series describes HPV vaccination as an off-label adjuvant therapy for actinic keratosis (AK). Methods: Twelve immunocompetent AK patients underwent HPV vaccination at a private dermatology clinic in Naestved, Denmark. Prior to vaccination, all patients demonstrated a high AK burden that required regular control visits. At 0, 2, and 6 months, the patients received an intramuscular injection of a commercially available 9-valent HPV vaccine. Concurrently, patients continued conventional AK therapies at 3-month intervals. Clinical response, consisting of reduction in AK number and general change in skin appearance, was assessed by a dermatologist over 12 months following first vaccination. Results: All patients (mean age 76.2 years; 10 M and 2 F) completed the vaccine schedule. Overall, an average 85% reduction in total AK burden was recorded 12 months after beginning vaccination. Median AK burden thus fell from 56 (IQR: 44-80) to 13.5 (IQR: 1-18) lesions after 12 months. Lesion reduction was observable by the second inoculation at month 2 (34 AKs; IQR 22-80), continuing steadily until month 6 (15 AKs; IQR 5-30) and plateauing between 6 and 12 months. Clinically, HPV vaccination elicited fading of lesions' erythematous background after the first dose, often followed by sloughing of hyperkeratotic elements in subsequent weeks. Patients reported no adverse effects related to HPV vaccination. Conclusion: This case series introduces the possibility that 9-valent HPV vaccination in combination with conventional treatments may be used as a therapeutic strategy for AK.